Psychometric Properties of ADHD Rating Scale—5 for Children and Adolescents in Sudan—School Version - Alhossein, Abdulkarim; Abaoud, Abdulrahman Abdullah; Becker, David; Aldabas, Rashed; Bakhiet, Salaheldin Farah; Al Jaffal, Mohammed; Alsufyani, Manar; Abdu Elrahim, Nagda Mohamed; Alzrayer, Nouf (Frontiers in Psychology, 2022)
Abstract The ADHD Rating Scale-5 for Children and Adolescents, School Version has been adopted and validated to be used in assessing ADHD among school children within Western contexts. However, there are few assessment tools in use for identifying ADHD characteristics in children in Sudan. Therefore, this study aimed to investigate the psychometric properties of this rating scale in the context of Sudan. To accomplish this, data were collected on a sample of 3,742 school-aged children and adolescents as reported by their teachers. Psychometric properties can be classified as very good, with very high reliability (> .90), and high construct validity tested by exploratory and confirmatory factor analysis. Thus, the ADHD Rating Scale—5 for Children and Adolescents, School Version is valid, reliable, and suitable to use for assessing ADHD symptoms among children and adolescents in the Sudanese context.